Development of Collaterals to the Spinal Cord after Endovascular Stent Graft Repair of Thoracic Aneurysms. Issue 6 (December 2016) - Fukui, S.; Tanaka, H.; Kobayashi, K.; Kajiyama, T.; Mitsuno, M.; Yamamura, M.; Ryomoto, M.; Miyamoto, Y.
Abstract : Objectives: In thoracic and thoraco-abdominal aortic aneurysm repair, spinal cord injury (SCI) is devastating. Detection of the Adamkiewicz artery might be important for preventing SCI. Although thoracic endovascular stent grafts often occlude the segmental artery, the incidence of SCI in thoracic endovascular aortic repair is thought to be low compared with open repair. This study aimed to evaluate how the Adamkiewicz artery is supplied after segmental arteries are occluded by stent grafts. Methods: From March 2007 to August 2015, 32 patients were enrolled whose segmental arteries that were connected to the Adamkiewicz arteries were occluded by stent grafts. Segmental arteries, Adamkiewicz arteries, collateral circulation into the Adamkiewicz arteries, and anterior spinal arteries were pre- and post-operatively evaluated by computed tomography angiography. Results: Post-operatively, Adamkiewicz arteries were detected in 24 (75%) patients, except for two patients with paraplegia and six without paraplegia. Post-operative Adamkiewicz arteries were the same as pre-operative Adamkiewicz arteries, except for one Adamkiewicz artery that was located at two vertebral levels below the pre-operative level. SCI occurred in two (6.3%) patients. The distribution of feeding arteries into the Adamkiewicz artery post-operatively was divided into three patterns as follows: a segmental artery below the distal landing zone of the stent graft (53%), branches of the left subclavian artery (33%), and a branch of the left external iliac artery (13%). Conclusions: The length of the stent graft should be as short as possible. Blood supply to the left subclavian artery should be maintained because segmental arteries below the segmental artery occluded by the stent graft and branches of the left subclavian artery can become collaterals post-operatively.